Collaborative aspects for installing e-business in a maintenance environment - Fröhner, Klaus-Dieter; Zabel, Jürgen (Business: Theory and Practice, 2007)
Business engineering process improvement is required because of the complexity of production and changing markets. Therefore, a multi-level-model is being developed by which it is possible to examine not only the enterprise level of the business processes, but also the person-oriented level. The philosophy was to bring together visions, tools and assistance as well as experienced personnel and different companies with different views and flexible organizations. This leads to a systematic, person-oriented distinction and integration of maintenance processes within collaborative structures, and an approach concerning the continuous improvement of the processes considering person-oriented abilities as cognitive constraints. The implicit knowledge of the executive persons is normally not integrated in existing business process analysis and therefore will be considered and integrated for the business engineering process improvement of maintenance activities.